DNAG #1. Subdivisions of the Superior Province of the Canadian Shield - Card, K.; Ciesielski, André (Geoscience Canada, 1986)
Abstract Past attempts to subdivide the Canadian Shield into provinces and subprovinces have relied primarily on variations in structural trends and styles, and to a lesser degree on isotopic ages of rock units and events. In the Superior Province, subdivisions based on all, or combinations of, structural trends and styles, lithology, absolute and relative ages of rock units and events, metamorphic grade,metal logenesis, and geophysical characteristics, leads to recognition of several different types of litho-tectonic domains, including volcano-plutonic, metasedimentary, plutonic, and high-grade gneiss subprovinces. These are considered to represent the primary components assembled in the Late Archean to form the Superior Province craton. The Superior Province is thus seen to consist of northern and southern high-grade gneiss terrains, in part at least of Early Archean age, and a broad central region consisting of elongate, east-west trending volcano-plutonic and metasedimentary subprovinces.